Extrapulmonary associations of health status in severe asthma and bronchiectasis: Comorbidities and functional outcomes. (July 2019) - Cordova-Rivera, Laura; Gibson, Peter G.; Gardiner, Paul A.; Hiles, Sarah A.; McDonald, Vanessa M.
Abstract: Background: Severe asthma and bronchiectasis are heterogeneous diseases that contribute to disability beyond the pulmonary system. The magnitude of the impact that these extrapulmonary features has on health-related quality of life (HRQoL) is unknown. Methods: We analysed the cross-sectional relationships between HRQoL (St. George's Respiratory Questionnaire; SGRQ) and extrapulmonary characteristics, including physical activity (steps/day), anxiety and depression, isometric leg strength, systemic inflammation, and several comorbidities in adults with severe asthma (n = 70) and bronchiectasis (n = 61). Results: Participants with severe asthma and bronchiectasis had similar SGRQ total scores (mean scores 43.7 and 37.8 for severe asthma and bronchiectasis; p  > 0.05), and similar pulmonary and extrapulmonary characteristics. The associations between extrapulmonary variables and HRQoL did not differ according to diagnosis (all interactions p  > 0.05). Greater anxiety and depressive symptoms, fewer steps/day and greater systemic inflammation were statistically associated with poorer HRQoL in both diseases ( p  < 0.05). Lower isometric leg strength in severe asthma, and greater Charlson Comorbidity Index in bronchiectasis were also associated with poorer HRQoL ( p  < 0.05). In the multivariable regression model performed in the combined disease groups, anxiety and depression, steps/day, systemic inflammation and isometric leg strength remained independently associated with HRQoL. Associations between extrapulmonary characteristics and SGRQ domains were stronger for the activity and impact domains, than symptoms. Conclusion: In severe asthma and bronchiectasis, extrapulmonary features including physical activity and leg strength have a significant impact on HRQoL, especially within the activity and impact domains. These features should be considered as part of the assessment of these conditions, and they may represent additional treatment targets to improve HRQoL. Graphical abstract: Image 1 Highlights: Extrapulmonary traits in severe asthma & bronchiectasis are associated with health-related quality of life (HRQoL). Associations (extrapulmonary traits/HRQoL) did not differ according to diagnosis. Physical activity & leg strength are significant HRQoL predictors in these diseases. Systemic inflammation & anxiety/depression symptoms are also predictors of HRQoL. These extrapulmonary traits may represent treatment targets to improve HRQoL.